STEM electron tomography in the Scanning Electron Microscope. (September 2015) - Ferroni, M; Signoroni, A; Sanzogni, A; Sberveglieri, G; Migliori, A; Ortolani, L; Christian, M; Masini, L; Morandi, V
Abstract: The scanning-transmission imaging mode in the SEM allows for the threedimensional tomographic reconstruction of a specimen, starting from a set of projection images. Compressed sensing was used to solve the undetermined problem of structure reconstruction and was proven capable of overcoming the limitations arising from the sampling scheme. Reconstructions of cobalt particles within a carbon nanotube and collagen fibrils in a dermal tissue are presented, demonstrating the potential of this technique in the set of 3-D electron microscopy methods for both physical and biological science.